Analisis Instrumen Kebijakan Fiskal terhadap Pertumbuhan Ekonomi di Provinsi Aceh - Syarifah Azzahra; Nurjannah Nurjannah; Iskandar Iskandar (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of fiscal policy instruments on economic growth in Aceh Province using independent variables such as regional taxes, employee expenditure, and indirect expenditure. The data were obtained from official publications of the Central Bureau of Statistics (BPS) Aceh in the form of time series covering the period 2009–2023. The analysis was conducted using multiple linear regression with the assistance of Eviews 12 software to ensure accurate and reliable results. The findings reveal that, partially, regional taxes have a positive but insignificant effect on economic growth in Aceh Province. Employee expenditure also shows a positive yet insignificant effect, while indirect expenditure has a negative and insignificant impact. Simultaneously, the three independent variables do not demonstrate a significant influence on regional economic growth. These results indicate that the effectiveness of fiscal instruments at the regional level remains limited and has not been able to provide a strong impetus for economic growth. Therefore, a comprehensive evaluation of the planning, allocation, and utilization of fiscal policies is necessary to ensure that Aceh’s economic development strategies become more targeted, efficient, adaptive, and capable of promoting inclusive and sustainable growth.